A survey of information needs and information and library use of faculty and students in five theological seminaries in the Philippines - Parulan, Nimfa B.; Hidalgo, Namnama P.; Miller, Janet (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1974)
This study reports the information needs and information and library use of faculty and students in five ATESEA-member theological seminaries in the Philippines.
Involved in this investigation were the libraries as well as the thirty faculty members engaged in teaching, research and extension programs and 192 students enrolled during the second semester of the school year 1982-1983 and are residing on the seminary campus of the Lutheran Theological Seminary, the Philippine Baptist Theological Seminary, the Saint Andrew's Theological Seminary, Far East, and the Union Theological Seminary.
The descriptive-survey method of research was used in this study employing a questionnaire constructed by the researcher and interviews as tools in gathering data. Brochures, handbooks, catalogues, and other records were also consulted. Mean scores were computed and transmuted to percentage equivalents. They were ranked and the percentage formula and point rank value system were used.
Findings showed that the population of the theological seminaries surveyed is international in nature with a majority of the students coming from the Philippines and other Asian countries and a majority of the faculty members coming from the west. There is also a wide range of students' ages which can be attributed to the programs that the seminaries offer and the fact that many of the students have served their own churches in different capacities before coming to the seminary.
The types of information theological seminary faculty and students need conform with the purposes they have for information-search which is closely related to their respective academic status, too. Both faculty and student respondents cited general background information as a need in keeping up-to-date and that they prefer to get it in printed forms.
The respondents showed relative satisfaction with their respective seminary library resources as well as with the outcome of their information-search. The faculty showed a more independent strategy in searching for the information they need while the students were more inclined to consult or ask for the help of others. Seminary students visit the library more often than the faculty members because aside from using the library resources, the students find the library an ideal place for study and concentration. At times, faculty members and a considerable number of students use other libraries' resources to satisfy their information need. Encyclopedias, dictionaries, lexicons, handbooks, commentaries, periodicals, indexes, and bibliographies were indicated as the most useful sources of information. Although, colleagues and peers have been cited helpful in obtaining needed information.
Findings also showed that the resources of each of the five seminary libraries rated adequate to very adequate on areas the respondents regarded as important. Suggestions were given by the respondents to improve the library services and develop the collection for maximum use.
In conclusion, both faculty and student respondents are found to use the library resources and its services extensively to satisfy their academic as well as personal information needs. They give the library a high regard as it seems to meet their basic information needs. Colleagues and peers prove to be helpful, too. Faculty and students use the information they gather as background for curricular purposes or in connection with research projects, lectures, sermons or speeches and the they prefer to get them in printed form. Respondents suggested a system of inter-library cooperation, a reference librarian, a union list of holdings and the improvement of the audio-visual collection.
Recommendations are given in the areas of reader services, library facilities, inter-library cooperation and collection development.
Typescript.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Theological seminary libraries -- Information services -- Philippines